Micro-CT Imaging of Pediatric Thyroglossal Duct Cysts: A Prospective Case Series - Frauenfelder, Claire; Shelmerdine, Susan C.; Simcock, Ian C.; Hall, Andrew; Hutchinson, John Ciaran; Ashworth, Michael T.; Arthurs, Owen J.; Butler, Colin R. (Frontiers in Pediatrics, 2021)
Objectives: To determine the feasibility of micro-CT as a high-resolution 3D imaging tool for thyroglossal duct cysts and to evaluate its role augmenting traditional histopathological examination of resected specimens. Methods: A single centre, prospective case series of consecutive children undergoing excision of a thyroglossal duct cyst was performed at a quaternary paediatric referral hospital in the United Kingdom. Consecutive children listed for excision of a thyroglossal duct cyst whose parents agreed to participate were included and there were no exclusion criteria. Results: Surgically excised thyroglossal duct cyst or remnant specimens from five patients (two males, three females) were examined using micro-CT alongside traditional histopathological examination. In all cases, micro-CT imaging was able to demonstrate 3D imaging datasets of the specimens successfully and direct radio-pathological comparisons were made (Figures 1–5, Supplementary Video 1). Conclusions: The study has shown the feasibility and utility of post-operative micro-CT imaging of thyroglossal duct cysts specimens as a visual aid to traditional histopathological examination. It better informs the pathological specimen sectioning using multi-planar reconstruction and volume rendering tools without tissue destruction. In the complex, often arborised relationship between a thyroglossal duct cyst and the hyoid, micro-CT provides valuable image plane orientation and indicates proximity of the duct to the surgical margins. This is the first case series to explore the use of micro-CT imaging for pediatric thyroglossal duct specimens and it informs future work investigating the generalizability of micro-CT imaging methods for other lesions, particularly those from the head and neck region where precisely defining margins of excision may be challenging.